The role of elected and appointed village leaders in the allocation of public resources: Evidence from a low-income region in China - Mu, Ren; Zhang, Xiaobo (International Food Policy Research Institute, 2011)
Based on primary survey data collected over two election cycles in a mountainous area in China, where an administrative village consists of several natural villages, this paper examines whether or not elected village heads and appointed Communist party secretaries favor their own natural villages when distributing public resources. The analysis shows clear evidence of favoritism by both village heads and party secretaries. In a subsequent election, incumbent village heads who have shown strong favoritism are likely to lose, but resource distribution does not seem to affect the likelihood of the reappointment of a party secretary.